Some bilinear inequalities through a weighted Hardy operator - Benaissa, B.; Sarikaya, M.Z. (Carpathian Mathematical Publications, 2025)
In this paper, we give some new generalizations of the bilinear Hardy type inequality by using weighted mean operator $S:=Sf_{v}$ and its dual $\widetilde{S}:=\widetilde{S}f_{v}$, where $f$ is a non-negative integrable function with two variables on $(0,+∞)×(0,+∞)$ and $v$ is a weight function.